Strategic Planning of Information Technology Architecture in Schools Using The Open Group Architect Framework (TOGAF) Case Study: SMA Negeri 15 Bandar Lampung - Absor, M Ulil; Sutedi, Sutedi (CV. Publikasi Indonesia, 2024)
This research aims to design an enterprise architecture at SMA Negeri 15 Bandar Lampung using the TOGAF ADM framework. This research involves several phases: Preliminary Phase, Architecture Vision, Business Architecture, Information System Architecture, and Opportunities and Solutions. In the Preliminary phase, the objectives and benefits of architectural development are determined to meet the needs of the school, including the new student enrollment system and network structure. The Architecture Vision phase describes the organization's profile, vision and mission, as well as the current state of architecture. Business Architecture analyzes key business processes using the value chain, including student admission, teaching and learning activities, and student release. Information System Architecture develops data and application architectures to support business vision and architecture. The Opportunities and Solutions phase identifies opportunities for information technology development to improve school operational efficiency. The results show that the implementation of TOGAF ADM can provide systematic and comprehensive guidance in designing enterprise architecture that suits the needs of schools.